Re-irradiation for progressive Diffuse Intrinsic Pontine Glioma (DIPG): The Spanish experience - Elena Panizo-Morgado; Felisa Vazquez-Gómez; Marta Perez-Somarriba; Miriam Pavon-Mengual; Andrés Morales-La Madrid; Blanca Lopez-Ibor; Palma Solano; Blanca Martinez de las Heras; Marta Cortés-Hernández; Miguel García-Ariza; Roberto Carlos Raynero-Mellado; Marta Martinez-Merino; et al. (EJC Paediatric Oncology, 2024)
Introduction: Diffuse intrinsic pontine glioma (DIPG) is the most common malignant brainstem tumour in children. Despite advances in understanding its biology, current treatments have shown minimal impact on overall survival in this fatal disease. Focal radiotherapy (RT) is the only treatment proven to improve symptoms and extend progression-free survival. Albeit palliative, re-irradiation (rRT) has emerged as the best alternative for progressive disease. This study presents the Spanish experience with re-irradiation in DIPG. Results: Between April 2015 and December 2023, 44 paediatric patients with progressive DIPG underwent rRT in 16 Spanish institutions. Median time from diagnosis to progression was 9.9 months (range, 4.2–24.3 months). Median dose of rRT was 20 Gy (range, 18–40 Gy) in 2 Gy fractions (range, 1.3–4 Gy). Twenty-two patients (50 %) received other treatments besides RT. Clinical improvement was seen in 77.3 %, and radiological improvement in 60 %. Treatment was well tolerated (1 case toxicity >grade 2 related to rRT). Median overall survival was 15.5 months (range, 8.2–63.2 months), with a median time from rRT to death of 4.2 months (range, 0.6–10.3 months). Longer time between diagnosis and rRT (>10 months) and dose of rRT >20 Gy were statistically significantly correlated with better overall survival. There was no survival benefit in patients receiving additional treatments. Conclusions: Re-irradiation is safe and effective in progressive DIPG patients, not only improving symptoms but also prolonging survival. However, the ideal candidates for rRT remain undefined, as well as the best irradiation scheme. Prospective studies are needed.